2019
DOI: 10.1038/s41467-019-08711-2
|View full text |Cite
|
Sign up to set email alerts
|

The short-chain fatty acid pentanoate suppresses autoimmunity by modulating the metabolic-epigenetic crosstalk in lymphocytes

Abstract: Short-chain fatty acids (SCFAs) have immunomodulatory effects, but the underlying mechanisms are not well understood. Here we show that pentanoate, a physiologically abundant SCFA, is a potent regulator of immunometabolism. Pentanoate induces IL-10 production in lymphocytes by reprogramming their metabolic activity towards elevated glucose oxidation. Mechanistically, this reprogramming is mediated by supplying additional pentanoate-originated acetyl-CoA for histone acetyltransferases, and by pentanoate-trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
236
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(267 citation statements)
references
References 51 publications
4
236
2
1
Order By: Relevance
“…Journal of Experimental Medicine expression in regulatory B cells (Luu et al, 2019). Interestingly, gut microbiota-derived short-chain fatty acids have also been shown to induce Th1 cells to produce IL-10 to maintain intestinal homeostasis, through the activation of STAT3 and mTOR, upstream of Blimp-1 up-regulation .…”
Section: Saraiva Et Almentioning
confidence: 99%
“…Journal of Experimental Medicine expression in regulatory B cells (Luu et al, 2019). Interestingly, gut microbiota-derived short-chain fatty acids have also been shown to induce Th1 cells to produce IL-10 to maintain intestinal homeostasis, through the activation of STAT3 and mTOR, upstream of Blimp-1 up-regulation .…”
Section: Saraiva Et Almentioning
confidence: 99%
“…Other SCFA also have immunoregulatory activities. Pentanoic acid (pentenoate) is present in high concentrations in SPF, but not GF feces (62). Pentenoate induces IL-10 in lymphocytes by elevating glucose oxidation, a function mediated by increasing acetyl CoA for histone acetyl transferase and activating mTOR.…”
Section: Scfasmentioning
confidence: 99%
“…In turn, changes in the relative abundance of key taxa correlated with shifts in intestinal levels of IL‐23/Th17‐related cytokines and beneficial short‐chain FAs such as propionic acid, linked to Treg cell expansion and abrogation of gut inflammation . In the fungal community, changes in Candida correlated positively with sIgA and negatively with valeric acid, which has been associated with IL‐10 production and reduction of IL‐17A . Moreover, metagenomic analysis demonstrated that treatment with IL‐17i was associated with up‐regulation of l ‐tryptophan biosynthesis.…”
Section: Discussionmentioning
confidence: 95%